2011
DOI: 10.1016/j.virol.2011.03.015
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of the cell cycle dependent association of the bovine papillomavirus E2 protein and ChlR1

Abstract: It has been shown that the genomes of episomally maintained DNA viruses are tethered to host cell chromosomes during cell division, facilitating maintenance in dividing cells. The papillomavirus E2 protein serves this mechanism of viral genome persistence by simultaneously associating with chromatin and the viral genome during mitosis. Several host cell proteins are reported to be necessary for the association of E2 with chromatin including the cohesion establishment factor ChlR1. Here we use fluorescence reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…TopBP1 and TopBP1; it could also be due to the natural stickiness of E2 to beads used in these coimmunoprecipitation experiments (14,18). What is clear from this experiment is that E2…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…TopBP1 and TopBP1; it could also be due to the natural stickiness of E2 to beads used in these coimmunoprecipitation experiments (14,18). What is clear from this experiment is that E2…”
Section: Resultsmentioning
confidence: 97%
“…Lanes 6 to 10 dem- WT interacts well with endogenous TopBP1, whereas mutant 8 is severely compromised, as shown in lane 5. The shadow band observed may indicate some residual binding, but there may also be a contribution to this from the "stickiness" of E2 for the beads (14,18 WT with no squelching at higher levels, and there is a significant difference between E2 TopBP1 and E2 WT activity at 10 ng of input plasmid. These results demonstrate that E2 TopBP1 is folded correctly and can bind to target DNA sequences and that there are differences between the transcriptional activation properties of this mutant and E2…”
Section: Resultsmentioning
confidence: 99%
“…WRN, BLM, and RECQ1) (32), suggests that that the ability of ChlR1 to disrupt protein-DNA complexes is biochemically unusual and may be important for its cellular function to preserve fork structure necessary for sister chromatid cohesion and/or participate in DNA repair or other processes. For example, ChlR1 was shown to be required for papillomavirus E2 protein loading onto mitotic chromosomes during DNA replication for the viral genome to be maintained and segregated (19,43). The functions of the ChlR1 motor ATPase in this process are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The actual mechanisms through which the E2 protein tethers papillomaviral episomes to host chromosomes are the subject of intense debate [46]. Using synchronised live cells, Feeney et al [47] have shown that the DNA helicase ChlR1 is required for the association of BPV-1 E2 with chromosomes. In their recent paper, the authors proposed that ChlR1 is required for loading the E2-associated viral genomes onto chromosomes during the S-phase, but not for their retention during mitosis.…”
Section: Bpv Persistence Latency and Transmissionmentioning
confidence: 99%